Dampak Desentralisasi Fiskal terhadap Perekonomian Antar Daerah: Analisa Model IRIO - Nurkholis, Nurkholis; Brodjonegoro, Bambang P. S. (UI Scholars Hub, 2003)
Regional autonomy program is the fonn of fiscal decentralization policy in Indonesia, legally started with the Jaw of Regional Government No.2211999 about de-concentration azas, which imply power or authority sharing and No.25/1999 about decentralization, which imply financial sharing between central and regional government. Financial sharing is tax and natural resources sharing revenue. This financial sharing type can widen fiscal gap between regions. As the solution, the central government gives block grants. Interregional Input-Output (IRIO) model can be used to analyze the impact of fiscal decentralization policy on sectoral and regional linkages, multipliers, growth, equalization, and efficiency of the regional economy. The analysis use shock variables of inter-governmental transfer including tax sharing revenue, natural resources revenue and block grants. They are treated as an exogenous variable package by regional government expenditure. The expenditures are in the form of investment and consumption based on IRIO model to analyze the optimality of policy variation. The analysis shows that the optimality of growth, equalization, and economic efficiency will be reached if the allocation of inter-governmental transfer is exactly the same as the potency and linkages between sectors and regions. We find the current formulation of intergovernmental transfer by central government, potent to increase regional disparity. Central government should refonnulate division of inter-governmental transfer to avoid fiscal decentralization to be contra productive policy